Optimized collagenase biosynthesis (Bacillus siamensis strain Z1) and its application in collagen hydrolysate-mediated silver and zinc oxide nanoparticles synthesis and characterization with antibacterial, antioxidant and cytotoxic activities - Archana G. Revankar; Zabin K. Bagewadi; Ibrahim Aljaezi; Omaish S. Alqahtani; Neha P. Bochageri; Bassam S. M. Al Kazman; Ibrahim Ahmed Shaikh; Basheerahmed Abdulaziz Mannasaheb; Muskan M. Naik (PLoS ONE, 2026)
Globally, environmental pollution caused by resilient protein like collagen is escalating due to inefficient disposal practices. Accumulation of collagen waste poses ecological threat, necessitating management strategies. Current study discloses collagenolytic bacterium, Bacillus siamensis strain Z1, isolated from marine water (Goa) demonstrating collagen breakdown and inducing collagenase biosynthesis. Production kinetics revealed optimal collagenase production (4.55 U/mL) on 2 nd day with a protein content of 0.69 mg/mL. Influence of physiochemical parameters, including inoculum size, metal ions, carbon and nitrogen sources, pH and temperature on collagenase yield was optimized achieving 17.93 folds enhancement by central composite design. Silver (AgNP) and Zinc oxide (ZnONP) nanoparticles were biosynthesized using collagen hydrolysate derived from marine collagen through collagenase action and characterized using UV-Visible spectroscopy, Fourier Transform Infrared Spectroscopy, X-ray Diffraction, Scanning Electron Microscopy with Energy Dispersive X-ray, Thermogravimetric Analysis and Atomic Force Microscopy elucidated thermostability, structure and surface characteristics. Antibacterial effect of nanoparticles was observed against B. cereus and E. coli . AgNP and ZnONP demonstrated antioxidant properties assessed by ABTS and DPPH assays. AgNP and ZnONP exhibited cytotoxicity on MCF-7 breast cancer cell lines, with IC 50 values 8.87 µg/mL and 25.21 µg/mL respectively. The study highlights biotechnological potential of collagenase in generating bioactive products for therapeutical and biomedical advancements.